New polymer bearing hydroxamic acid chelating resin for binding of heavy metal ions - Lutfor, M.R.; Silong, S.; Yunus, W.M.Z.W.; Rahman, M.Z.A.; Ahmad, M.; Haron, M.J. (Scientific Reviews Ltd., 2001)
A new polymer containing the hydroxamic acid functional group was prepared from poly(methyl acrylate) grafted sago starch and the binding capacities of copper, iron, chromium, nickel, dysprosium, gadolinium and uranium were found excellent; other metal ions have significant sorption capacities.